2016
DOI: 10.1530/eje-16-0358
|View full text |Cite
|
Sign up to set email alerts
|

The link between metabolic features and TSH levels in polycystic ovary syndrome is modulated by the body weight: an euglycaemic–hyperinsulinaemic clamp study

Abstract: Our data confirm that the prevalence of SCH is increased in PCOS women. The presence of SCH is associated with endocrine and metabolic imbalances of PCOS, and the excessive body weight seems to promote this interplay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
(37 reference statements)
3
21
0
2
Order By: Relevance
“…However, these associations lost their significance after adjustment for confounding factors. Consistently, a recent study found an association between thyroid function and metabolic parameters in obese patients with polycystic ovary syndrome (PCOS), while this association disappeared in non-obese PCOS patients ( 38 ). These results might suggest that the link between thyroid function and metabolic features is modulated by body weight.…”
Section: Discussionsupporting
confidence: 56%
“…However, these associations lost their significance after adjustment for confounding factors. Consistently, a recent study found an association between thyroid function and metabolic parameters in obese patients with polycystic ovary syndrome (PCOS), while this association disappeared in non-obese PCOS patients ( 38 ). These results might suggest that the link between thyroid function and metabolic features is modulated by body weight.…”
Section: Discussionsupporting
confidence: 56%
“…The majority of studies used the Rotterdam criteria for PCOS diagnosis and only one study used the ESHRE/ASRM criteria. Subjects included in the meta-analysis were from five different countries including Spain ( 17 ), India ( 22 ), Italy ( 20 , 23 ), Brazil ( 21 ), and China ( 24 ), while those only included in systematic review were from America ( 25 ), India ( 26 ), China ( 27 ), Brazil ( 16 ), and Iran ( 28 ). Definition for SCH varied among studies, with TSH cut-off values ranging from 2.5 to 5 mIU/L.…”
Section: Resultsmentioning
confidence: 99%
“…Since the prevalence of SCH differs from geographic region, ethnicity or age, the results of studies were inconsistent. Only 14.3% of participants had SCH in the Italian PCOS population ( 23 ), whereas 27.0% of participants had SCH in China ( 24 ). The reported prevalence of SCH in the Indian PCOS population was nearly 22.5% ( 22 ), which was higher than that in Brazil ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…TSH düzeyi ile estradiol (E2) ve seks hormon bağlayıcı globulin düzeyleri arasında da negatif korelasyon bulunmuştur. 40 SH'li kadınlarda PKOS oranı da yüksek olarak saptanmıştır. İlişkili olarak SH'de menstü-rasyon düzensizlikleri sık görülmekte ve fertilite indeksi düşmektedir.…”
Section: Subkli̇ni̇k Hi̇poti̇roi̇di̇ Ve İnsüli̇n Di̇renci̇ Metaboli̇k Sendromunclassified